Mizahi Cinaslı Bir Risale - Öztoprak, Nihat (İlim Yayma Cemiyeti, 2000)
There is a plenty of original pamphlets that shows the richness of our culture and literature in Turkish handwritten journal s found in libraries. In this article, one of these pamphlets is introduced. This is a two page-long humorous pamphlet in which same words are used in different meanings for the effete of homour. Introduction, the definition of pun (cinas) and its kinds have been given. lts place within the literary arts is also defined. Following this, having dealt with the language, style, and arrangement features, puns have been selected and sorted out according to its kinds. At the end, the manuscript it given in transcription and a vocabulary is added.
A Pamphlet with Humorous Pun
Keywords: Literature; Turkish Culture; Art of Pun; Homour; Manuscript Journal